Unveiling the Potential of Rhizosphere Bacteria from Plumeria acuminata Tree as Plant Growth-Promoting Rhizobacteria - Diajeng Ukhty Mahirro; Triastuti Rahayu (Scientiae Educatia: Jurnal Pendidikan Sains, 2023)
The rizosphere bacteria are known to have the characteristics of Plant Growth Promoting Rhizobacteria (PGPR). From the rhizosphere of the Cambodian white tree at the Pracimaloyo Cemetery in Surakarta, 43 bacterial isolates have been obtained. Bacterial isolates have the ability to produce IAA up to 113.58 ppm. Publications related to the Cambodian tree rizospheric bacteria from the found burial site require further PGPR characterization tests because the characters as PGPR include IAA, N fixation, the antagonism of the pathogen, the ability to produce siderofores, ACC deaminases, and non-pathogens to host plants that are proven to have hypersensitive reactions, so this study aims to characterize the isolate of Cambodgian bacteria as the PGPR in improving the nitrogen and hypersensor reactions (HR). A total of 40 isolates of Cambodian tree rizosphere bacteria were tested for their ability to repair N2 by measuring the concentration of ammonia formed using spectroscopic photometer methods, while the HR test used tobacco plants. The ability to measure nitrogen shows that as many as 11 isolates (26.82%) are capable of producing NH3 (ammonia). The highest ammonia concentrations are produced by P8 isolates at 13.815 mM and P2 at 10.523 mM. Of the 41 rhizospheric bacterial isolates tested for hypersensitivity, 18 showed positive responses. A positive response to the HR test is characterized by symptoms of necrosis on tobacco leaves. The rhizosphere bacteria from the Cambodian trees in the cemetery have the potential to repair nitrogen, and 23 isolations show no symptoms of necrosis.